THE JOURNAL ANALES DE PSICOLOGÍA FROM A HISTORIOGRAPHIC VIEWPOINT: THE FIRST DECADE OF A PUBLICATION WITH ACADEMICAL ROOTS (1984-1994) - Sánchez Hernández, Antonio; Quiñones Vidal, Elena; Cameo Olcina, Mercedes (Anales de Psicología / Annals of Psychology)
In this paper, the first decade of existence of the journal Anales de Psicología (1984-1994) is analyzed. This journal was initially forum of expression of researchers from the University of Murcia., but it soon acquired a national and international character, taking into account the collaboration and demanding for publications in their pages. Through these years, the journal has covered a wide range of topics, promoting the participation of authors from most Spanish universities, as well as some from abroad. The articles published in this journal show a constant degree of collaboration, as it can be seen either in the number of authorships per article, or in the collaboration index found (2’1). The study of the references cited in the articles indicates a general attention to Psychology as a whole, showing a good update of the literature used for the elaboration of the articles (with a half-life of 7’84 years).